Efeito agudo do fumo na variabilidade da frequência cardíaca e da sua cessação no transporte mucociliar - Ito, Juliana Tiyaki [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Despite stricter antismoking campaigns in several countries, is estimated to 1.25 billion adults are smokers and the projection is a new epidemic that may lead to 1 billion tobacco-related deaths during the 21st century. Damages caused by smoking mainly affect the respiratory system, however, it is also considered an important risk factor for cardiovascular disease. It is known that the smoking intensity and its chronicity contribute to a worsening of impairment caused by smoking, and that smoking cessation becomes a crucial milestone to avoid these progressions as well as to reduce morbimortality due to tobacco-related diseases. Aims: This Master’s thesis aimed to evaluate the acute smoke exposure effect in the autonomic modulation of adult smokers and to investigate if the smoking status and age influence in this response, and to evaluate the smoking cessation effect on mucociliary clearance and in exacerbation frequency of smokers with chronic obstructive pulmonary disease (COPD). Methods: For the first aim, we evaluated heart rate variability (HRV) of adults smokers, participants of the smoking cessation program at FCT/UNESP, in smoke and recovery from this exposure moments (30 minutes after smoking)...

Introdução: Apesar das rigorosas campanhas contra o fumo em muitos países, estimase que 1,25 bilhões de adultos sejam tabagistas e a projeção é de uma nova epidemia que pode levar a 1 bilhão de mortes tabaco-relacionadas durante o século 21. Os danos causados pelo tabagismo afetam principalmente o sistema respiratório, entretanto, também é considerado um importante fator de risco para doenças cardiovasculares. Sabe-se que a intensidade do fumo e sua cronicidade contribuem para um agravamento dos prejuízos causados pelo tabagismo, e que a cessação do tabagismo torna-se um marco crucial para evitar tais progressões assim como para reduzir a morbimortalidade por doenças tabaco-relacionadas. Objetivos: Esta dissertação teve como objetivos: avaliar o efeito da exposição aguda ao fumo na modulação autonômica de tabagistas adultos e investigar a influência da condição tabagística e da idade nesta resposta, além de avaliar o efeito da cessação tabagística no transporte mucociliar e na frequência de exacerbações em tabagistas com doença pulmonar obstrutiva crônica (DPOC)...
Keywords: Fisioterapia; Fumo - Vicio; Sistema nervoso; Mucosa nasal; Physical therapy